Early Post-operative Outcomes of Single versus Multiple Arterial Grafts in Coronary Artery Bypass Grafting; A Comparative Analysis - Chaudhry, Imtiaz Ahmed; Ali, Nasir; Afzal, Sidra; Bashir, Imran (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare early post-operative outcomes of Single versus Multiple Arterial grafts in Coronary Artery Bypass Grafting (CABG) surgery. Study Design: Analytical Cross-sectional study. Place and Duration of Study: Adult Cardiac Surgery, Armed Forces Institute of Cardiology/National Institute of Heart Diseases Rawalpindi Pakistan, from Jul 2022 to May 2023. Methodology: One hundred and forty nine patients planned for elective isolated CABG (with two or more grafts) were enrolled in study using consecutive sampling. They were allocated into two groups, group A (Multiple Arterial CABG group) and group B (Conventional CABG group). Data was collected on early post-op outcomes i.e. ICU stay, ventilation time, inotropic duration, chest drainage, rhythm complications including Supraventricular Tachycardia (SVT) and mortality using a structured proforma. Chi-square and t-test were applied to make comparison between both groups. p<0.05 was considered statistically significant. Results: Out of one hundred and forty nine patients, who underwent elective CABG, majority were males 124(83.2%). Mean age of the patients was 59.18±9.28 years. Seventy four (49.7%) patients underwent Multiple Arterial CABG while 75(50.3%) had conventional CABG. Mean ICU stay duration was 56.74±48.30 hours in group A while it was 67.25±73.42 hours in group B; p=0.30. Mean Chest Drainage was 622.05±505.69 ml in group A while it was 846.13±799.67 ml in group B; p=0.04. Mean ventilation time was 10.28 ± 19.88 hours.................. Conclusion: The use of the Radial Artery (RA) in CABG surgery was associated with better early ...............